2010
DOI: 10.1021/bm100755x
|View full text |Cite
|
Sign up to set email alerts
|

Sorption Efficiency of Chitosan Nanofibers toward Metal Ions at Low Concentrations

Abstract: Chitosan fibers showing narrow diameter distribution with a mean of 42 nm were produced by electrospinning and utilized for the sorption of Fe(III), Cu(II), Ag(I), and Cd(II) ions from aqueous solutions. The ion concentrations in the supernatant solutions were determined using inductively coupled plasma-mass spectrometry (ICP-MS). The filtration efficiency of the fibers toward these ions was studied by both batch and microcolumn methods. High efficiency in sorption of the metal ions was obtained in the both me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 59 publications
(93 reference statements)
2
45
0
Order By: Relevance
“…Those results of the immobilized enzyme stability presented hereinbefore can be interpreted in terms of the size of the metal ions and electric density which could further determine the coordination capability between the chelate fiber ligand and the metal ions. According to Lewis theory [29] and Pearson rules [30], metal ions, which have small size, high positive electric, low polarization ability, and the property of being difficult to be deformed, are called hard acid. Hard acid such as Fe .…”
Section: Operational Stabilitymentioning
confidence: 99%
“…Those results of the immobilized enzyme stability presented hereinbefore can be interpreted in terms of the size of the metal ions and electric density which could further determine the coordination capability between the chelate fiber ligand and the metal ions. According to Lewis theory [29] and Pearson rules [30], metal ions, which have small size, high positive electric, low polarization ability, and the property of being difficult to be deformed, are called hard acid. Hard acid such as Fe .…”
Section: Operational Stabilitymentioning
confidence: 99%
“…For example, in agricultural irrigation pipes, the filtering material is placed on a cross-section of the pipes such that it is normal to the flux direction of solution, and as such the mechanical resistance to the continuous flow becomes the main requirement for filtering material. In this sense, electrospun fiber mat may be a promising candidate for such applications [28].…”
Section: Introductionmentioning
confidence: 99%
“…13 Among these coating methods, electrospinning has the ability to fabricate micro/nanobers, to control morphology and for orientation of nanobrous mat. [14][15][16] The applicability of electrospun bers as SPME sorbent for the extraction of both nonpolar and polar compounds was reported by Zewe et al 17 and it was found that the electrospun polymeric negative photoresist, SU-8 2100, ber coated wires displayed the best performance with low detection limits and large linear ranges for phenolic compounds. Bagheri and Aghakhani evaluated polyurethane and polyaniline-nylon-6 electrospun bers for the extraction of chlorobenzenes.…”
Section: Introductionmentioning
confidence: 90%